The equilibrium crystal shape of strontium titanate: Impact of donor doping. (15th January 2017) - Rheinheimer, Wolfgang; Altermann, Fabian J.; Hoffmann, Michael J.
Abstract: The present study investigates the impact of point defect concentrations on the equilibrium crystal shape of strontium titanate. Therefore the shape of intergranular pores in coarse microstructures was observed. The point defect concentration was changed by donor-doping with Niobium (0.2 at.%–2.4 at.%). A decreasing surface energy anisotropy was found with increasing donor dopant concentration and with increasing temperature. These findings are correlated to the defect chemistry and grain growth behavior of strontium titanate. Graphical abstract: